Application of new electrode materials in N-type OFET - Liu Haokun; Liang Qiangbing; Hao Yang; Zhang Ye; Li Zhanfeng; Ji Ting; Li Guohui; Hao Yuying; Cui Yanxia (Dianzi Jishu Yingyong, 2022)
Compared with traditional field effect transistor, OFET has the advantages of simple preparation process, low cost, flexibility, transparency and so on. It is widely used in flexible electronic products, wearable devices and other fields. As an important part of OFET devices, electrodes affect the overall performance of OFET devices. In order to improve the performance of the electrode, on the one hand, the metal electrode can be modified, on the other hand, new materials such as polymer can be used to make OFET electrode. This paper reviews the application of new electrode materials in N-type OFET. Firstly, the general device structure is introduced. Then the development of N-type OFET using modified metal electrode, polymer electrode, carbon based electrode, inorganic compound electrode and nanowire electrode is introduced. Finally, the full text is summarized, and the future development of OFET new electrode materials is prospected.